DEVELOPING GRAMMAR SUB-SKILL THROUGH MODERN AND INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN LANGUAGE TEACHING (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article bargains with the issues related to creating communicative competence of future English instructors. It considers the idea that creating communicative competence can advantage not as it were to the intuitively competences of the learner from the instructive point of see, but moreover psycho-emotional characteristics and socio-cultural advancement of a understudy as a individual. As we know, communicative competence is the capacity meaning connection successfully with others and competence is caught on as a combination of dialect abilities an person has for learning a remote dialect. Such potential contributes to his/her achieving tall levels of execution. This paper reflects the taking after: the hypothesis of communicative competence and a few of its models; the significance of creating communicative competence of understudies who are future English instructors and the suggestions of communicative competence in English dialect educating and learning. Furthermore, the work recommends the fundamental methodic standards of creating communicative competence of future English instructors.